Penerapan Kebiasaan Menyanyikan Lagu Nasional dalam Menanamkan Sikap Cinta Tanah Air pada Siswa Sekolah Dasar - Novi Nuriyah Ulfa; Habibah Annisa Az-zahra; Amelia Dirgahayu; Iin Mayasiroh; Nazala Fadlila R; Sulistiyawati Sulistiyawati; Aliatun Najah; Dewi Lestari (Lembaga Pengembangan Kinerja Dosen, 2026)
This study identificates the importance of singing national songs as an effort to foster a sense of patriotism among elementary school students in the era of globalization and the 4.0 industrial revolution. The weakening of nationalism among the younger generation today implies that strategies for strengthening nationalism in schools must be changed. The focus of this investigation is to examine the influence of national songs in shaping the spirit of nationalism among students. Using a descriptive qualitative method at SD Negeri 3 Menganti in Jepara Regency, data was collected through direct observation and interviews with teachers and students. The findings of the study revealed that the routine of singing the Indonesian national anthem and the Jepara march every morning succeeded in fostering discipline, pride in the homeland, and increased self-confidence among students. Although there were some obstacles in the form of a lack of mastery of the lyrics by some students, the school responded with intensive guidance and facility support. Overall, this study concluded that the consistent combination of national and local songs is a character-building and strategic educational tool in the early absorption of national values.